Campesino, granjero, proletario: formación de clase en una economía cafetalera de pequeños propietarios 1850-1950 - Gudmundson, Lowell (Revista de historia., 1990)
Analyzes class formation in Costa Rica between 1850 and 1950. The agricultural sector of Costa Rica society witnessed the transition from “peasant to farmer”, that is, transformation of peasantry engaged in subsistence activities to a sector of landowners and landless people, entrepreneurs and works.